EFFECTS OF MUHAMMAD ABDUH IN MALAYAN-INDONESIA ARCHIPELAGO - Amir, Ahmad Nabil (IAIN PONOROGO, 2021)
Muhammad Abduh mempunyai pengaruh dan dampak yang kukuh dan luar biasa di kepulauan Nusantara. Karya-karya dan ideanya sangat berpengaruh dan kekal bertahan di rantau ini dengan kesannya yang meluas dalam landskap politik dan sosialnya. Beliau telah memberikan impak yang mendalam terhadap pergerakan Islam moden seperti Persyarikatan Muhammadiyah, Jam‘iyah al-Irsyad, Persatuan Islam (Persis), Pensyarikatan Ulama, Hizbul Muslimin, dan Sarekat Islam. Tafsir al-Manar-nya telah memberi pengaruh yang jelas kepada karya-karya tafsir yang terhasil di Nusantara, seperti Tafsir al-Azhar, Tafsir al-Qur’anul-Karim, dan sebagainya. Majalah al-Manar yang diilhamkan oleh Muhammad Abduh dan Rashid Rida telah memberikan inspirasi dan pikiran dasar terhadap banyak berkala dan akhbar yang berorientasikan reform yang menyalin dan menerjemahkan tulisan-tulisannya seperti majalah al-Munir, al-Imam, al-Ikhwan, Saudara, dan lainnya. Justeru, makalah ini bertujuan meninjau pengaruh Abduh yang ekstensif dalam kebangkitan gerakan pembaharuan di Arkipelago Melayu. Kajian ini berbentuk studi kualititif dari jenis penelitian pustaka dengan metode analisis kandungan. Data yang terkumpul dianalisis secara deksriptif dan analitik. Penemuan kajian membuktikan bahawa Muhammad Abduh mempunyai pengaruh yang signifikan terhadap harakat pembaharuan (tajdid) dan tradisi rasional yang berkembang di kepulauan Melayu-Indonesia.[Muhammad Abduh had a remarkably profound and lasting impact in South East Asia. His works and ideas were highly influential in the region with strong repercussion in its political and social landscape. He had strongly impacted the movements of Muhammadiyah, al-Irsyad and Persatuan Islam (Persis). His Tafsir al-Manar had broke the ground with rational outlook that influence major works of tafsir such as Tafsir al-Azhar, Tafsir al-Quranul Karim, and others. The Majallah al-Manar planned and initiated by Muhammad Abduh had significantly inspired many reform oriented works and periodicals such as journal al-Imam, al-Munir, al-Ikhwan, Saudara, al-Dhakhirah al-Islamiyah and Seruan Azhar. Thus this paper attempts to survey Abduh’s extensive influence and its impact on Islamic reform (tajdid) in the Malay Archipelago. The method of study is based on qualitative approaches, using content analysis method. It was conducted based on library research to investigate the related data that was subsequently analyzed using descriptive-analytical approaches, The finding concluded that Muhammad Abduh had deep influence in religious reform and rational tradition that flourished in the Malay-Indonesian Archipelago.]